Correlation Between Age and Knowledge Among The Student of SMP "X" with The Occurrence of Free Sex - Dani Naseri; Arifani Cahyani; Helena G. Manalu; Vanny Angellina (Journal of Medicine and Health, 2018)
Free sex behavior is sexual activity conducted outside of marriage, considered as a socialproblem for the community and at risk of transmitting the disease. The aim of this study was todetermine the relationship between age and knowledge of junior high school students "X" againstthe occurrence of free sex. This is an analytic observasional study with cross sectional approach.We collected data from 146 respondents aged 11-19 years. Data was analyzed using chi-squarestatistic test with Î± = 0,05. The study was conducted on junior high school students "X" inPurwakarta Regency Indonesia. The results showed that there was a significant correlationbetween age with the occurrence of free sex (p = 0,000), but there was no significant correlationbetween knowledge (p = 0,250) with the occurrence of free sex in junior high school students "X".The research shows that as many as 7.54% of junior high school students "X" claimed to havesexual intercourse. We concluded that there is a correlation between the age of junior high schoolstudents "X" with the occurrence of free sex, but there is no significant relationship between theknowledge of the students SMP "X" with the occurrence of free sex.Keywords: knowledge of free sex, free sex, age